Estrus synchronization with Cloprostenol and effect off ollitropin treatment on superovulatory response and embryo recovery in Sahiwal Cows - MISHRA, O P; KHAN, J R; AWASTHl, M K (The Indian Journal of Animal Reproduction, 2002)
Estrus was synchronized in 18 donors and 28 recipient cows with two injection of 500μgm cloprostenol 11 days apart. Follitropin was administered in three different doses viz 400 mg NIH, 300mg NIH and 200mg NIH to donors(n=l 8) which were randomly and equally divided in three groups,A.B and C. Significantly (p<0.05) higher mean owlation was recorded in group B(l0.00± 1.06) as compared to group A (4.16±0.6) and group C (5.16 ± 0.47). Significant difference was recorded (p<0.05) for recovery of mean total embryo in group B (5.00 ± 0. 78) as compared to group A (1.66 ± 0.59) and group q2.5 ± 0.68). Similarly, significantly (p<0.05) higher mean transferable embryo recovery was obtained in group B ( 4.00±0.68) than group A (1.00±0.36) and group C (2.17±0.17). Follitropin at the dose rate of300 mg NIH proved most effective in terms of mean owlation, mean total embryo recovery and mean transferable embryo recovery in Sahiwal cows.